2018
DOI: 10.12659/msm.907084
|View full text |Cite
|
Sign up to set email alerts
|

Salvianolic Acid B Suppresses Inflammatory Mediator Levels by Downregulating NF-κB in a Rat Model of Rheumatoid Arthritis

Abstract: BackgroundSalvianolic acid B (SB) is a major active phyto-component of the plant Radix Salvia miltiorrhiza, which is traditionally used to treat joint pain and arthritis. The present study examined the anti-rheumatoid arthritis efficacy of SB on collagen-induced rheumatoid arthritis (CIA) in a rat model.Material/MethodsForty-eight rats were divided into 4 groups: Control rats treated with saline (Group I), rats subjected to CIA induction by intradermal injection of bovine collagen II type at the tail (Group II… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 44 publications
(53 reference statements)
2
24
0
Order By: Relevance
“…Firstly, Wang and Liu 37 reported that activation of NF-κB signaling contributed to the occurrence of inflammation-related IBS-diarrhea. In addition, recently, we detected that NF-κB signaling was also implicated in IBS-related hyperalgesia in an unpublished research, consistent with previous studies reporting that NF-κB signaling participated in the pain modulation in inflammatory diseases, 38 cancer, 39 and autoimmune diseases, 40 via the release of inflammatory cytokines such as IL-1β, IL-6, and TNF-α. Moreover, our findings indicate that the excitatory effect of CHT1 in GI motility is closely associated with increased ACh release.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Firstly, Wang and Liu 37 reported that activation of NF-κB signaling contributed to the occurrence of inflammation-related IBS-diarrhea. In addition, recently, we detected that NF-κB signaling was also implicated in IBS-related hyperalgesia in an unpublished research, consistent with previous studies reporting that NF-κB signaling participated in the pain modulation in inflammatory diseases, 38 cancer, 39 and autoimmune diseases, 40 via the release of inflammatory cytokines such as IL-1β, IL-6, and TNF-α. Moreover, our findings indicate that the excitatory effect of CHT1 in GI motility is closely associated with increased ACh release.…”
Section: Discussionsupporting
confidence: 90%
“…Colorectal distension (CRD) was then conducted after 20 minutes of adaptation. Each recording progression consisted of a 5-minute predistention baseline activity measurements, a 20-second CRD-evoked response (20,40,60, and 80 mmHg), and a 3-minute postdistention activity measurement, followed by a 3-minute rest between 2 CRD episodes. The EMG signals expressed by visceromotor response (VMR), the area under the curve in response to the CRD stimuli, were collected and analyzed using Lab Chart 7 software (AD instruments).…”
Section: Electromyogram Measurementsmentioning
confidence: 99%
“…It is currently used as one of the therapeutic agents for RA and has been reported to be effective [56]. Thus, targeting NF-κB is effective at maintaining bone mass during inflammation [13][14][15][34][35][36][37][49][50][51][52][53][54][55][56][58][59][60][61][62][63][64][65][66][67][68][69]85,[91][92][93][94], and there is a possibility for "killing two birds with one stone". However, embryonic lethality has been reported in mice where molecules involved in the NF-κB signaling have been knocked out [26][27][28][29][30][31], and it is necessary to consider the possibility of causing serious side effects simply by inhibiting NF-κB.…”
Section: Discussionmentioning
confidence: 99%
“…There are various stages of BMP/Smad signaling, but the classical NF-κB pathway does not affect the phosphorylation of Smad1/5 or the formation of the Smad1-Smad4 complex; however, the classical NF-κB pathway does interfere with the DNA binding complex. Furthermore, we found that the p65 subunit of the classical NF-κB pathway associates with Smad4 but not Smad1 [64]. Therefore, when the association sites of p65 and Smad4 were examined, the transactivation domain 2 (TA2) of p65 and the mad homology (MH) 1 region of Smad1 were directly associated.…”
Section: The Activation Of Nf-κb Suppresses Bone Formationmentioning
confidence: 98%
See 1 more Smart Citation